Fluxomics - New Metabolomics Approaches to Monitor Metabolic Pathways - Emwas, Abdul-Hamid; Szczepski, Kacper; Al-Younis, Inas; Lachowicz, Joanna Izabela; Jaremko, Mariusz (Frontiers in Pharmacology, 2022)
Fluxomics is a new omics research field that measures the rates of all intracellular fluxes in the central metabolism of biological systems. Fluxomics is one of the most relevant approaches to investigate metabolic phenotypes. Metabolic flux using 13C-labeled molecules is increasingly used to monitor metabolic pathways. By determining metabolic pathways, researchers can probe the corresponding gene-RNA and protein-metabolite interaction networks in actual time. Thus, fluxomics can be used to understand metabolic pathways and has many applications in biotechnology and pharmacology. Here, we briefly introduce fluxomics with a review of the most recent studies and common analytical tools.